Open non‐microsurgical, laparoscopic or open microsurgical varicocelectomy for male infertility: a meta‐analysis of randomized controlled trials - Ding, Hui; Tian, Junqiang; Du, Wan; Zhang, Liyuan; Wang, Hanzhang; Wang, Zhiping (BJU international, 2012)
Study Type – Therapy (systematic review) Level of Evidence 1a What's known on the subject? and What does the study add? There are several surgical techniques for the treatment of varicocele in infertile men, including open non‐microsurgical, laparoscopic and microsurgical varicocelectomy. It is currently unclear, however, which is the most beneficial method for patients. The present meta‐analysis found that microsurgical varicocelectomy is the most effective and least morbid method among the three varicocelectomy techniques for treating varicocele in infertile men. OBJECTIVE • To compare various techniques of open non‐microsurgical, laparoscopic or microsurgical varicocelectomy procedures to describe the best method for treating varicocele in infertile men. PATIENTS AND METHODS • We searched PubMed, Embase, the Cochrane Library, the Institute for Scientific Information (ISI) – Science Citation Index and the Chinese Biomedicine Literature Database up to June 2011. Only randomized controlled trials (RCTs) were included in the present study. • The outcome measures assessed were pregnancy rate (primary), the incidence of recurrent varicocele, time to return to work, the incidence of postoperative hydrocele and operation duration (secondary). • Two authors independently assessed the study quality and extracted data. All data were analysed using Review Manager (version 5.0). RESULTS • The present study included four randomized controlled trials comprising 1,015 patients in total. • At the follow‐up endpoints, patients who had undergone microsurgery showed a significant advantage over those who had undergone open varicocelectomy in terms of pregnancy rate (odds ratio [OR]= 1.63, 95% confidence interval [CI]: 1.19–2.23]. • There was no significant difference between laparoscopic and open varicocelectomy (OR = 1.11, 95% CI: 0.65–1.88) or between microsurgery and laparoscopic varicocelectomy (OR = 1.37, 95% CI: 0.84–2.24). • The incidences of recurrent varicocele and postoperative hydrocele were significantly lower after microsurgery than after laparoscopic or open varicocelectomy. • The time to return to work after microsurgery and laparoscopic varicocelectomy was significantly shorter than that after open varicocelectomy. • The operation duration of microsurgical varicocelectomy was longer than that of laparoscopic or open varicocelectomy. CONCLUSIONS • Current evidence indicates that microsurgical varicocelectomy is the most effective and least morbid method among the three varicocelectomy techniques for treating varicocele in infertile men. • More high‐quality, multicentre, long‐term RCTs are required to verify the findings.